Targeting diabetes pathways: an in silico study of bioactive compounds from Mitragyna speciosa leaf extract - Begum, Taslima; Ahmed, Qamar Uddin; Arzmi, Mohd Hafiz; Shah, Syed Adnan Ali; Rofiee, Mohd Salleh; Sarian, Murni Nazira; Helal Uddin, A.B.M.; Khattak, Muhammad Muzaffar Ali Khan (IIUM Press, 2025)
Background: The rapid expansion of urbanization has triggered significant lifestyle shifts, most notably an increase in sedentary lifestyles and the widespread consumption of processed, nutrient-poor foods. These factors have been strongly implicated in the rising prevalence of Diabetes Mellitus. Current treatment strategies for diabetes remain heavily reliant on conventional pharmacotherapy, which often carries risks of drug tolerance and adverse effects. In this context, Kratom (Mitragyna speciosa), a traditional medicinal plant native to Southeast Asia and historically used to manage various ailments, presents a promising avenue for the development of novel antidiabetic agents.